PENGARUH GAYA HIDUP, BRAND IMAGE HALAL, CELEBRITY ENDORSER DAN TINGKAT HARGA TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH (STUDI KASUS PADA MAHASISWI PENDIDIKAN EKONOMI UNIVERSITAS NEGERI MAKASSAR) - Nur Ainun Syafri; Mustari Mustari; Muhammad Hasan; Muhammad Ihsan Said; Nurdiana Nurdiana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study is to partially and concurrently assess and analyze the effect of lifestyle, halal brand image, celebrity endorser, and price level on purchase decisions of Wardah cosmetics by economic education students at Makassar State University. The approach in this study is a quantitative approach with a sampling method using the slovin method. After being formulated, it is known that the number of samples in this study were 80 active female students from the 2017-2021 class of Economic Education Study Program, Faculty of Economics and Business, Makassar State University. Data collection techniques are through observation, questionnaires or questionnaires and documentation. Then it will be analyzed using descriptive analysis and multiple regression analysis using SPSS 25. In this study, it was found that the tests carried out at the Economic Education Study Program, Makassar State University partially, lifestyle variables, halal brand image, celebrity endorser and the price level of each variable affect the purchasing decision of Wardah cosmetics at Makassar State University Economic Education students. Meanwhile, simultaneously, lifestyle variables, halal brand image, celebrity endorser and price level together have a significant effect on the purchasing decision of Wardah cosmetics on Economic Education Students, Makassar State University.